Interim Analysis of STREAMLINE® Surgical System Clinical Outcomes in Eyes with Glaucoma - Lazcano-Gomez G; Garg SJ; Yeu E; Kahook MY (Clinical Ophthalmology, 2022)
Gabriel Lazcano-Gomez,1 Sumit J Garg,2 Elizabeth Yeu,3 Malik Y Kahook4 1Department of Glaucoma, Clínica Láser y Ultrasonido Ocular, Puebla City, Puebla, Mexico; 2Department of Ophthalmology, University of California Irvine, Irvine, CA, USA; 3Department of Ophthalmology, Virginia Eye Consultants, Norfolk, VA, USA; 4Department of Ophthalmology, University of Colorado, Aurora, CO, USACorrespondence: Malik Y Kahook, Tel +1 720 848 2500, Email malik.kahook@cuanschutz.eduPurpose: To characterize the clinical outcomes of a novel ab interno minimally invasive procedure with the STREAMLINE® Surgical System for creation of incisional goniotomies and canal of Schlemm viscodilation in eyes with mild to severe primary open-angle glaucoma (POAG).Methods: In a prospective, single-arm, first-in-human case series, 20 eyes of 20 subjects with mild to severe POAG underwent creation of incisional goniotomies and canal of Schlemm viscodilation following phacoemulsification cataract extraction after washout of all intraocular pressure (IOP)-lowering medications. The angle surgery portion was performed with a single-use handpiece tipped with a microcannula that creates precise goniotomies through the trabecular meshwork into the canal of Schlemm and delivers a small volume of ophthalmic viscosurgical device directly into the canal via precise catheterization. Outcomes in this interim analysis included mean reduction in IOP and medications through 6 months of follow-up, as well as the proportion of eyes achieving IOP reduction ≥ 20% from baseline.Results: At month 6, mean IOP reduction of ≥ 20% from baseline was achieved in 89.5% of eyes (17/19). Mean (standard deviation) medicated IOP at screening was 16.3 (3.6) mmHg and unmedicated baseline IOP (after washout) was 23.5 (2.5) mmHg. Mean IOP was significantly reduced from baseline through 6 months of follow-up to 14.7 (2.4) mmHg (p< 0.001), representing an IOP reduction of 8.8 mmHg (36.9%). Overall, 57.9% (11/19) of eyes decreased dependence on IOP-lowering medications by at least one medication, and 42.1% (8/19) were medication free. Mean medication use was reduced from 2.0 (0.8) at screening to 1.1 (1.1) at 6 months (p< 0.001). Three eyes had transient IOP spikes treated with topical medications.Conclusion: The creation of incisional goniotomies and canal of Schlemm viscodilation safely and effectively reduced IOP and the need for IOP-lowering medications by both clinically and statistically significant magnitudes in eyes with mild to severe POAG undergoing concomitant phacoemulsification cataract extraction through the first 6 months of follow-up.Keywords: trabecular meshwork, canal of Schlemm, viscodilation, MIGS, glaucoma, goniotomy